WOMEN'S SAFETY DEVICE: TECHNOLOGICAL ADVANCEMENT WITH ONE TOUCH AUTHENTICATION USING OPTICAL FINGERPRINT SCANNER - Muhammad Zamin Ali Khan; Muhammad Zulqarnain Siddiqui; Syed Arsalan Haider; Hafiza Amna Owais Ansari; Ujala Rehan (Spectrum of Engineering Sciences, 2025)
The issue of women's safety in our nation has emerged as a significant concern across various dimensions. The incidence of crimes targeting women is escalating at an alarming pace. As a result of these increasing threats, independent women are experiencing heightened feelings of insecurity, which restricts their capacity to lead fulfilling lives. In light of the critical challenges that women encounter in their everyday existence, we propose a rapid response mechanism that functions on a principle of “activation without user interaction.” This system is designed to be proactive, operating effectively in situations where the user may be incapacitated, thereby assisting women during unexpected threats. Should a woman find herself in a precarious situation, perceiving that someone with malicious intent is following her (for instance, in cases of potential sexual assault), or if she is uncertain about her route home, this device will safeguard her by notifying her contacts and a control center of her precise location and safety status through an Emergency SMS Alert. This strategy is consistent with earlier research, such as “TOUCH ME NOT – A Women Safety Device,” which underscores the importance of integrating smart sensing and alert systems to support women in crisis. Likewise, IoT-based solutions proposed in recent work highlight the significance of GPS tracking, GSM communication, and wearable safety modules as vital components of contemporary women's safety devices. This device not only offers assistance from family and law enforcement but also ensures rapid access to all available safety resources.